2016
DOI: 10.1097/sap.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity on Postoperative Complications After Breast Reconstruction Using Free Muscle-Sparing Transverse Rectus Abdominis Myocutaneous, Deep Inferior Epigastric Perforator, and Superficial Inferior Epigastric Artery Flap

Abstract: This review suggests that obesity increases the risk of both flap-related and donor-site complications in breast reconstruction using msTRAM, DIEP, and SIEA flaps. In comparison to conventional TRAM flaps, however, muscle-conserving abdominal flaps may have an advantage in reducing the morbidity in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
75
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 45 publications
2
75
1
Order By: Relevance
“…Ochoa and co‐workers demonstrated an increased risk of complications—both flap and donor‐site related with high BMI, especially in the severely obese patients (Ochoa et al, ). Other studies found similar results as obesity along with smoking are the strongest risk factor for delayed wound healing (Lee & Mun, ; Scheer, Novak, Neligan, & Lipa, ). In the current study 20% of the patients reported to be active smokers at the time of surgery.…”
Section: Discussionsupporting
confidence: 69%
“…Ochoa and co‐workers demonstrated an increased risk of complications—both flap and donor‐site related with high BMI, especially in the severely obese patients (Ochoa et al, ). Other studies found similar results as obesity along with smoking are the strongest risk factor for delayed wound healing (Lee & Mun, ; Scheer, Novak, Neligan, & Lipa, ). In the current study 20% of the patients reported to be active smokers at the time of surgery.…”
Section: Discussionsupporting
confidence: 69%
“…The latter seems to be obvious, considering that the scar might be under more tension and will be more prone to migrate cranially. On the contrary, obesity is a well‐documented predictor of an increased risk of flap‐related as well as donor site complications 20‐22 . As described by us previously, we consider patients with a normal to slightly elevated BMI, a local fat deposition in the lower abdomen and abdominal skin redundancy to qualify for an abdominal flap in particular 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Different studies reported that increased length of surgery is associated with increased rates of wound healing problems, and thus prolonged hospital stay. 11,12 Potentially due to nonsignificant differences of operative times, the patients of both of our study groups did not present significantly different complication rates. Additionally, our study could not demonstrate a difference between an experienced surgeon and a resident, fellow, or assistant in respect to donor-site closure and potential for subsequent wound healing problems.…”
Section: Discussionmentioning
confidence: 63%